2014
DOI: 10.4254/wjh.v6.i9.670
|View full text |Cite
|
Sign up to set email alerts
|

Skin toxicity predicts efficacy to sorafenib in patients with advanced hepatocellular carcinoma

Abstract: Skin toxicity was associated with favorable outcomes with sorafenib therapy for advanced HCC. Nursing intervention contributed to better adherence, which may improve the efficacy of sorafenib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…The severe adverse effects associated with sorafenib use, reported to occur in 50 % of patients [22], potentially influence HRQOL. Interestingly, skin toxicity [23], hypertension [24], and diarrhea [25] are known to be associated with better prognosis in sorafenib therapy. Therefore, the substantial anti-tumor effects of sorafenib might have countered severe adverse effects both physically and mentally.…”
Section: Discussionmentioning
confidence: 99%
“…The severe adverse effects associated with sorafenib use, reported to occur in 50 % of patients [22], potentially influence HRQOL. Interestingly, skin toxicity [23], hypertension [24], and diarrhea [25] are known to be associated with better prognosis in sorafenib therapy. Therefore, the substantial anti-tumor effects of sorafenib might have countered severe adverse effects both physically and mentally.…”
Section: Discussionmentioning
confidence: 99%
“…Some retrospective studies have shown in patients with advanced HCC treated with sorafenib a positive association with early skin drug-related toxicities and clinical benefit [42][43][44] and disease control [44,45] (Table 4). Recently, the Barcelonan group reported the results of a prospective single-arm, monocentric study that assessed the link between early sorafenib-related skin toxicities and outcome in patients with advanced HCC [46] .…”
Section: Clinical Biomarkersmentioning
confidence: 99%
“…Phase II and III trials in multiple tumor types have confirmed that nintedanib treatment is not associated with HFSR . However, HFSR is common during treatment with sorafenib, and it has been suggested that the presence of skin toxicity, including HFSR, may be a surrogate biomarker for sorafenib clinical efficacy . Hand–foot skin reaction can be severe, necessitating dose reductions or treatment discontinuation, and is thus a treatment concern .…”
Section: Discussionmentioning
confidence: 99%
“…(26,(28)(29)(30) However, HFSR is common during treatment with sorafenib, (8) and it has been suggested that the presence of skin toxicity, including HFSR, may be a surrogate biomarker for sorafenib clinical efficacy. (31,32) Hand-foot skin reaction can be severe, necessitating dose reductions or treatment discontinuation, and is thus a treatment concern. (8,31) There is speculation that sorafenibrelated HFSR may be due to the combined inhibition of several receptors, (33) specifically VEGFR, PDGFR, c-KIT, and Flt-3.…”
Section: Discussionmentioning
confidence: 99%